2014
DOI: 10.1089/neu.2013.3061
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Surgical Management after Spinal Cord Injury: Vasopressor Usage, Early Surgerys, and Complications

Abstract: The optimal mean arterial blood pressure for maintenance of spinal cord perfusion is not known. Our aim was to describe vasopressor usage and examine their effects in patients with spinal cord injury (SCI). We undertook a retrospective cohort study of 131 patients with SCI who received any kind of vasopressors to maintain blood pressure in the neurocritical care unit of a Level 1 trauma center (2005-2011). Vasopressor usage and complications were obtained from the medical record. Neurological outcomes were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 32 publications
0
85
1
Order By: Relevance
“…By comparison, Inoue et al reported complications with dopamine or phenylephrine usage such as arrhythmias, acidosis, and skin necrosis. 15 In our laminectomized patients, ISP was significantly higher in the supine than the lateral position by up to 8 mm Hg for cervical injuries and 18 mm Hg for thoracic injuries. This finding has important implications for nursing care: we recommend avoiding wound compression (e.g., by avoiding the supine position or by placing a ring-shaped pillow around the wound).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…By comparison, Inoue et al reported complications with dopamine or phenylephrine usage such as arrhythmias, acidosis, and skin necrosis. 15 In our laminectomized patients, ISP was significantly higher in the supine than the lateral position by up to 8 mm Hg for cervical injuries and 18 mm Hg for thoracic injuries. This finding has important implications for nursing care: we recommend avoiding wound compression (e.g., by avoiding the supine position or by placing a ring-shaped pillow around the wound).…”
Section: Discussionmentioning
confidence: 56%
“…25 Intervening to elevate the blood pressure without monitoring ISP and SCPP from the injury site is potentially dangerous due to cardiogenic complications. 15 From our experience with ISP/SCPP monitoring, and by analogy with the concept of individualized CPP opt in TBI, it seems that SCPP opt varies between patients, thus suggesting individualized SCPP management rather than setting generalized guidelines. 20 Currently, ICP monitoring and CPP optimization are the standard of care when managing severe TBI patients in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…20 In patients with acute traumatic central cord syndrome, high rates of cardiogenic complications are independently associated with dopamine and phenylephrine, and more serious complications were associated with dopamine use in elderly patients. 42 Higher complication rates have been reported when vasopressors were used contrary to guidelines: e.g., use of dopamine for injuries below T-6. 76 Interestingly, in a small study of 11 patients, norepinephrine was found to increase cord perfusion pressure by 2 mm Hg compared with dopamine, 2 which may be of clinical advantage in maintaining strict MAP goals during acute care.…”
Section: Spinal Cord Perfusion and Vasopressor Supportmentioning
confidence: 99%
“…Our findings thus challenge current guidelines, which recommend maintaining mean arterial pressure at 85 -90 mmHg for a week after TSCI 28 . Elevating mean arterial pressure after TSCI requires inotropic support, which is associated with several complications 29 . To reduce inotrope requirements and, therefore, inotrope-related complications when aiming for SCPP 90 -100 mmHg, expansion duroplasty could be performed to lower the ISP 8 .…”
Section: Annals Of Neurologymentioning
confidence: 99%